PENYAJIAN WAYANG ORANG LAKON KADHARMANING KUNTHI - Subono, Blacius (Acintya, 2015)
The presentation of wayang orang (man puppet) refers to the characterization existed in wayang kulit (leather puppet). The difference lies in the media of expression (man as three dimensions and puppets as two dimensions). The improvement of wayang orang movements is all forms of treatment changes done by the dalang or the lakon (story) composer. However, it is still closed to the previous story repertoire. This work raises the issue of how the creative process in arranging the script and text form of wayang orang lakon Kadharmaning Kunthi is. The thinking base of creativity is used to solve the problem. Creativity is not marked by imitation, adjustment, or binding on the existed pattern. Creativity involves ideas and imaginative action including: sensing, feeling, imaging, as well as searching and explanation of truth. Sensing means the absorption of sense which represents the starting point of artist to actualize creativity. Creativity is also based on feeling and emotion. Feelingalso occurs because of the mutual relationship between man and man, man and nature, man and things, and all events that happen in man life.Keywords: art works, wayang orang, creativity, Kunthi.